Methods families use to raise funds for anorectal malformation treatment at a single public referral hospital in Southwestern Uganda - Oyania, Felix; Eze, Anthony N; Ullrich, Sarah; Kotagal, Meera; Ozgediz, Doruk (World Journal of Pediatric Surgery, 2024)
Background: In Uganda, only two public hospitals provide pediatric surgery services. With less than 10 pediatric surgeons serving approximately 20million children in Uganda, most patients with anorectal malformations (ARMs) must make several trips to the hospital before undergoing surgery. As a result, households borrow money, sell assets, or solicit contributions from friends and relatives to meet healthcare expenses. We used a crosssectional study to examine methods families use to raise funds for the treatment of ARMs at a single institution in Southwestern Uganda. Methods: This cross-sectional study was conducted in the pediatric surgery unit at a Regional Referral Hospital/ University Teaching Hospital in Southwestern Uganda from June 2021 to July 2023. Participants included caretakers of children presenting with ARMs for treatment at our referral hospital. Results: A total of 157 participants were enrolled. Mothers were the main caregivers (77.9%) present at the hospital. Out of a median monthly household income of UGX200 000 (US$51.68), families spent a median of UGX50 000 (US$12.92) to travel to the hospital. To raise funds for healthcare expenses, 68% of households reported selling assets. Conclusion: Families sell household assets to afford ARMs treatment in Southwestern Uganda. Financial protection by the government through a national child health insurance policy would shield families from substantial health related expenditures and decrease this burden. In addition, targeted policy to strengthen pediatric surgical capacity through workforce expansion and skills training such as the Pediatric Emergency Surgery Course, may minimize costs, improve timeliness of care, and prevent case cancellations.
Keywords: Pediatric surgery services; Uganda; Anorectal malformation treatment